The influence of Van der Waals interaction on electronic structure of coupled graphene planes - V. V. Bolotov; V. A. Sachkov (Омский научный вестник)
The work is devoted to the study of the influence of the Van der Waals interaction on the electronic properties of the distance of paired graphene planes. Calculations are made of the «ab initio» the width of the band gap as a function of the van der Waals interaction, which is varied by shifting one plane relative to the other. The conditions for the formation of a forbidden band in the band structure of coupled graphene planes with the help of Van der Waals interaction are investigated. The results obtained are applicable for the analysis of the band structure of multi-walled carbon tubes containing defects.